Ergonomics and Tri Hita Karana on Balinese Traditional Houses Building - I Nyoman Artayasa (Institut Seni Indonesia Denpasar, 2021)
Tri Hita Karana is the concept of three things that can lead to happiness, which consist of the relation of human beings with God, amongst human beings, and the relationship of human beings with the environment, which is embodied in the circulation, the design space forming element, the supporting build a room, design of facilities, utilities and decoration. The study of ergonomics on traditional residential houses in Bali focuses on task elements, organization, and environment. The task examines how the facilities were created based on anthropometric and activity flow. Organization study about traditional Balinese buildings layout in terms of space organization resulted in a large scale, function space, and circulation space. Environment review the two sides, firstly is the physical environment, namely: the use of circulation, lighting and handling the current season every year, and secondly is the social environment, namely: religion, beliefs, norms, and others. There are similarities between Ergonomics and Tri Hita Karana; therefore, this study intends to it. It is conducted by using qualitative descriptive analysis with Tri Hita Karana concept on traditional Balinese buildings and accompanied with ergonomic values based on the subject of the task and environmental organizations. This writing aims to observe whether the ergonomics and Tri Hita Karana have similar views in the embodiment of traditional Balinese houses. At the end of the discussion, we can conclude that the embodiment of traditional Balinese residential buildings has to be considered on the relationship of human beings with God and the relationship between human beings and the environment. It also includes a consideration in ergonomics consists of task, organization, and environment; and it is found out that the concept of Tri Hita Karana has similarities with the idea of ergonomics on traditional Balinese houses.